Analysis and modelling of natech accidents originated by strong winds (2024)
This document presents a doctoral thesis regarding Natech (Natural Hazards Triggering Technological Disasters) accidents originated by strong winds impacting storage tanks. The main objective of this thesis is to develop a methodology to conduct analysis that includes a Natech risk approach in storage units located in coastal zones, because these areas are susceptible to extreme weather. In recent decades, the frequency of natural events has increased and, consequently, also following the simultaneous development of industrial activities in many countries, the frequency of Natech accidents has also increased. This phenomenon has activated the interest of researchers in the study of new methods of risk analysis to prevent and mitigate possible damage to populations, the environment, and processing facilities. In fact, the literature shows that there is an increasing awareness about natural events; specifically, in cases where they occur simultaneously, following a cascading effect, or cumulatively over time. For these reasons, in this document, research to conduct risk assessment is proposed including Natech risk due to strong winds. To achieve the objectives, some theoretical frameworks were consulted to know what the situation in each topic is. Additionally, a literature review was carried out to notice the principal gaps in Natech risk methodologies. In short, this document contains the following chapters: • Chapter 1 - Introduction: it presents an introduction about natural events (earthquakes, tsunamis, floods, lightning, strong winds, and so on) and how they have triggered technological accidents. In this way, potential domino effects of these accidents on process and storage plants are presented. Additionally, some representative cases of Natech events caused by strong winds are described, highlighting the fact that the case of strong winds has been much less studied than other natural events. As a particular case, the evolution of meteorological events in coastal zones of Colombia and its potential consequences for storage plants is discussed. Finally, the research problem, the scope of the research, objectives, innovative nature, and the structure of the document are presented. • Chapter 2 – Literature review: it presents systematic review of the Natech events literature under two approaches. The first one seeks to know the development about Natech risks analyses in order to identify gaps in this kind of analysis, and in the same way, to compare what the academic literature proposes in contrast with what the international agencies are applying in process units. The second one shows a comparative analysis of the existing Natech QRA approaches, highlighting features and differences and identifying main gaps that should be addressed in future research. • Chapter 3 –Wind effects on storage tanks: it deals with the effects of extreme winds on above-ground storage tanks designed under API-620 and API-650 standards. Some information about tank characterization, possible accidental scenarios, structural and natural hazard analysis, and storage tanks fragility analysis are discussed extensively. In this chapter, new event trees for damage modes of storage tanks impacted by strong winds are proposed. • Chapter 4 – Methodology for analysing the Natech risk: it presents a quantitative risk assessment methodology for storage tanks subjected to strong winds. This methodology has three main steps: 1) inclusion of strong winds as a hazard to the integrity of storage tanks in industrial facilities located in coastal zones, 2) evaluation of dispersion, fire, and explosion effects and their probability of occurrence, and 3) calculation of not only individual and societal risk, but also environmental and socio-economic risk. Additionally, a computational tool for the calculation of risk. The methodology is implemented in one case study. • Chapter 5 – Case study: it illustrates the application of the proposed methodology in a hypothetical case study. The coastal area chosen was the Colombian Atlantic coast, where there are crude and refined storage facilities belonging to national companies. In the case study, all the steps of the methodology are applied in detail and the potential of the developed computational tool is presented. • Chapter 6 – Conclusions and future work: it concludes the results of the thesis and explains the need to continue contributing to risk analysis methodologies that involve natural events. Additionally, this chapter explains the need to include uncertainty analysis in the estimates of frequencies, consequences and risks, both in current and new methodologies, to achieve results that are more accurate and reliable.